PENGARUH FAKTOR-FAKTOR PENGAMANAN BARANG MILIK DAERAH TERHADAP PENGAMANAN ASET TETAP PEMERINTAH KABUPATEN BENGKULU SELATAN - , Setio Renny ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research aims to analyze the upshot of goods owned local security factors, including administration security toward physical, legal security, and the influence of partially independent variable in securing fixed asset, jointly independent variable as well as to identify policy strategy in terms of securing fixed asset of Local Government of South Bengkulu. Thus, analysis instrument used is scale of likert and Analytical hierarchy process. Scale of likert is utilized to view perception of manager of goods owned local in securing fixed asset, while analytical hierarchy process is to view policy strategy considered the most crucial in securing local owned goods by Local Government, where the respondent is from executive and legislative side. The analysis technique, hence, used in the research is ordered regression model with error distribution logistic.Therefore, the research shows that the outcome of administration security toward physical, legal has jointly significant and positive effect. Concerning on the outcome of partially independent variable toward fixed asset security, the variable of physical security has the most powerful toward fixed asset security possessed by Local Government of South Bengkulu. Then, the effect of jointly independent variable toward fixed asset security has significant and positive influence where administration, physical and legal security provides 31,54% of the influence, while the rest of other value is explained by other variable of 68,46%. Moreover, policy strategy considered the most crucial by respondent is the administration security of inventorying/recording and the settlement of ownership proof.